Periodic solutions of quasi-linear impulse systems in a critical case - Akhmetov , M. U.; Perestyuk , N. A. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
Conditions for the existence of periodic solutions of weakly-nonlinear autonomous and nonautonomous impulse systems in the critical case are determined.